THE PROBLEMS OF COMMUNITY COHESION IN THE PERCEPTION OF YOUNG PEOPLE - SPĂTARU Tatiana (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
This study addresses from several perspectives the perception of young people regarding the problems of community cohesion. Social cohesion plays a decisive role in the ability to organize social groups, construction of harmonious social relations. The generation of the 21st century places a greater emphasis on social cohesion compared to the other generations. What barriers declare young people and how they see the future of a cohesive society in the Republic of Moldova, are the questions that find their interpretation. The empirical data were collected during the focus-groups with young people. The analysis of the synthesis of the answers has outlined the perceptions of young people regarding the problems of community cohesion. The epistemological interpretation of the research results suggests valuable conclusions regarding the correlation between young people and the construction of a cohesive society.